Self Esteem pada Remaja Korban Kekerasan dalam Pacaran di Kecamatan Krembung - Kurniawati, Anjar Haziziah; Fahmawati, Zaki Nur (ResearchJet Journal of Analysis and Inventions, 2024)
This study aims to describe the self-esteem of adolescent victims of dating violence, as well as the factors that influence the victim's self-esteem. This study uses a qualitative approach to the type of phenomenological research. The subjects of this study were 3 (three) adolescent victims of dating violence, namely AD, DR, and PT. The data collection method in this study used semi-structured interviews. Testing the validity of the data was carried out using the time triangulation method, which is a way to check the credibility of the data through semi-structured interview techniques with several research informants carried out under different conditions or times. The data analysis technique used is data reduction, data display, and then the data is verified as a research result. The results showed that there were similarities in the self-esteem of the three research subjects in terms of self-significance and benevolence, apart from that there were differences in the details of the forms of other aspects such as individual strengths and abilities as well as the factors that influenced them.